THE EFFECTIVENESS OF HERRINGBONE TECHNIQUE ON STUDENTS READING NARRATIVE TEXT AT THE TENTH-GRADE STUDENTS OF SMAN 1 KOTA MOJOKERTO IN ACADEMIC YEAR 2018/2019 - Yunita Dwi Wikandari (Universitas Islam Sumatera Utara, 2018)
This research was done to measure the effectiveness of herringbone technique on students reading narrative text at the tenth-grade students of SMAN 1 Kota Mojokerto in academic year of 2018/2019. This research used quantitative research design specifically quasi experimental post-test only design. The subject of this research was chosen from ten classes of the tenth grade in SMAN 1 Kota Mojokerto in academic year of 2018/2019. The researcher did cluster random sampling technique to gain the research subjects. Finally, the researcher got X-IPA 5 as the experimental class that would be taught by using herringbone technique and X-IPA 4 as the control class that would be taught using non herringbone technique. In the end of each treatment, the researcher gave post-test to both of groups that consisted of 50 multiple choice questions of narrative text comprehension to attain the data. After the data collected, the researcher analyzed the data using statistical formula of independent t-test that would present the difference between students’ score in learning reading using herringbone technique and without herringbone technique. Based on the calculation result, the researcher found that the t value t table that is 4, 833 1,669 with the significant level 5 %. It meant that the Null Hypothesis (Ho) was rejected, and the Alternative Hypothesis (Ha) was accepted. It can be said that there is significant difference between the students taught using herringbone technique and those not. In conclusion, the herringbone technique is an effective technique for teaching reading narrative text at the tenth-grade students of SMAN 1 Kota Mojokerto in academic year of 2018/2019.